Timing of transition from open-pit to underground mining: A simultaneous optimisation model for open-pit and underground mine production schedules. (August 2022) - Chung, Joyce; Asad, Mohammad Waqar Ali; Topal, Erkan
Abstract: Generally, shallow deposits are mined through open-pit mining and where the deposits are extended to a substantial depth, there is a potential for a combination of open-pit and underground mining methods. In this case, mine planning and optimisation play a significant role in the decision-making. This paper proposes a mixed-integer programming model to obtain the optimal transition point and the transition period from open-pit to underground mining, maximizing the project net present value considering crown pillar placement and development cost. An implementing at a three-dimensional case study generates the optimal transition point and period and an optimal production schedule for both open-pit and underground operations. The implementation considers three scenarios: transition point only (scenario 1), transition point and period without production delay (scenario 2), and transition point and period with two-period production delay during the transition (scenario 3). The optimal transition point for scenario 1 is 315 m and for scenarios 2 and 3 is 360 m below the surface. Highlights: A new mixed integer programming based model for transition-point problem in mining. Simultaneous optimisation of open-pit and underground mine production schedules. Application of the model at hypothetical and realistic case studies.